Impact of climate change on malaria in Africa: a combined modelling and observational study. (April 2017) - Endo, Noriko; Yamana, Teresa; Eltahir, Elfatih A B
Abstract: Background: Africa is the hotspot for malaria transmission where more than 90% of malaria deaths occur every year. The effect of climate change on malaria transmission in Africa has been controversial. Malaria is a major vector-borne parasitic disease transmitted to humans by Anopheles spp mosquitoes. Malaria transmission is an intricate function of climatic factors, which non-linearly affect the development of vectors and parasites. In this study, we aimed to project that the risk of malaria will increase towards the end of the 21st century in east Africa, but decrease in west Africa. Methods: We combine a novel malaria transmission simulator, HYDREMATS, that has been developed based on comprehensive multi-year field surveys both in east Africa and west Africa, and the most reliable climate projections through regional dynamical downscaling and rigorous selection of global circulation models from among CMIP5 models. Findings: We define a bell-shaped relation between malaria intensity and temperature, centered around a temperature of 28°C. Future risks of malaria are projected for two highly populated regions in Africa: the highlands in east Africa and the fringes of the desert in west Africa. In the highlands in east Africa, temperatures are substantially colder than this optimal temperature; warmer future climate exacerbate malaria conditions. In the Sahel fringes in west Africa, temperatures are around this optimal temperature; warming is not likely to exacerbate and might even reduce malaria burden. Unlike the highlands in east Africa, which receive major amounts of annual rainfall, dry conditions also limit malaria transmission in the Sahel fringes in west Africa. Interpretation: The study shows disproportionate future risk of malaria due to climate change between east and west Africa, and should have an effect on guiding strategies for climate adaptation over Africa. Funding: Cooperative agreement betweenUS National Science Foundation and Cooperative Agreement between theMasdar Institute of Science and Technology (Masdar Institute), Abu Dhabi, UAE, and theMassachusetts Institute of Technology (MIT), Cambridge, MA, USA .